2006
DOI: 10.1063/1.2388925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the adsorbate stiffness on the resonance response of microcantilever sensors

Abstract: The authors present a theoretical model to predict the resonance frequency shift due to molecule adsorption on micro-and nanocantilevers. They calculate the frequency shift experienced by cantilevers made of either silicon or the polymer SU-8, when two adsorbates, myosin protein and an alkanethiol, are attached to the cantilever surface. They demonstrate that the effect of the adsorbate stiffness can be comparable or even larger than the mass effect, producing positive frequency shifts. The results provide met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
154
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(159 citation statements)
references
References 13 publications
4
154
0
1
Order By: Relevance
“…This is necessary to obtain i) a correct quantification of the amount of target in the sample and ii) for obtaining those parameters that allow optimization of the sensor response. Recently, we have found that in addition to the added mass, nanomechanical resonators are very sensitive to the stiffness of the adsorbed molecules [12,13]. The problem is that both effects produce opposite shifts of the resonant frequency being detrimental to the sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…This is necessary to obtain i) a correct quantification of the amount of target in the sample and ii) for obtaining those parameters that allow optimization of the sensor response. Recently, we have found that in addition to the added mass, nanomechanical resonators are very sensitive to the stiffness of the adsorbed molecules [12,13]. The problem is that both effects produce opposite shifts of the resonant frequency being detrimental to the sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…A key piece in this approach is a model that accounts for the effect of the stiffness of the biological particles on the recorded jumps in the resonant frequencies. So far, the only model that accounts for this effect assumes that the adsorbate length is much larger than its thickness and hence the adsorbate can effectively be approximated by a thin layer on a cantilever region 12 . The case of single biological entities, such as proteins and viruses, is significantly more challenging.…”
mentioning
confidence: 99%
“…The resonance frequency of the cantilever can be quantified by equaling the mean potential and kinetic energies per oscillation cycle, referred to as Rayleigh-Ritz method 12 ,…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1A), which is fundamentally unachievable by exclusive use of existing nanoscale electrical or mechanical biosensors. Moreover, the reliance of change in stiffness (23,24) ensures screening-free detection of charged/neutral molecules, with no need for a reference electrode, and the measurement of drain current for detection requires no complex instrumentation. It should be noted that from a mechanical perspective, the Flexure-FET operates close to pull-in instability, a critical point.…”
mentioning
confidence: 99%